Voltage Optimal Control Strategy for Distribution Networks with Multiple Integrated Photovoltaic and Energy Storage Machines - Jinglin HAN; Ping HU; Ruosong HOU; Zhiyong CHEN; Hongtao LI; Yuanyuan CHAI (Zhongguo dianli)
The access of large-scale distributed photovoltaic (PV) into distribution networks (DNs) can easily cause voltage violation problem, posing a threat to the safe and stable operation of DNs. Therefore, a voltage optimal control strategy that combines the centralized optimization and distributed real-time control is presented for DNs with multiple integrated PV and energy storage (ES) machines. Firstly, a centralized rolling optimization model is established to formulate the voltage and power references of PV-ES machine in the next period. Then, a distributed voltage real-time control method is proposed using the voltage sensitivity coefficients to develop the local reactive power droop curve, distributed reactive power support and local active power control logic. Finally, the IEEE 33-node system is used to verify the feasibility and effectiveness of the proposed control strategy. The proposed voltage control strategy can effectively solve the voltage violation problem, and possess the adaptive voltage regulation ability under real-time fluctuations of source-load power.